The 1897 Colonial Invasion of Benin and the Minimalist Policy of the British Government - Edigin, Collins Osayuki (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This study examines the role of the British government in the colonial invasion of Benin in 1897. It discusses the attitude of the British government towards the colonial acquisition of Benin. The study argues that contrary to the widely held notion in colonial literature, the British government had little interest in colonial adventures in West Africa. This informed the delegation of governmental powers to the consular officials to enable them to protect the interest of British merchants in the region. However, the British government was drawn into the engagement after the massacre of some consular officials by Benin soldiers. This resulted in the punitive invasion of Benin in 1897.